2011
DOI: 10.3174/ajnr.a2725
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Blood Flow Measurements in Gliomas Using Arterial Spin-Labeling at 3T: Intermodality Agreement and Inter- and Intraobserver Reproducibility Study

Abstract: BACKGROUND AND PURPOSE:QUASAR is a particular application of the ASL method and facilitates the user-independent quantification of brain perfusion. The purpose of this study was to assess the intermodality agreement of TBF measurements obtained with ASL and DSC MR imaging and the interand intraobserver reproducibility of glioma TBF measurements acquired by ASL at 3T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Compared with other ASL acquisition times in recently published data, which ranged from 3 minutes, 26 seconds, to 5 minutes, 52 seconds, this results in an acceleration factor of approximately 3.5. 13,18 This acceleration was achieved as the result of the reduction of measurement repetitions to 25 rather than the formerly suggested 50 repetitions. 11,12 This was accomplished by the signal intensification of intravascular blood flow compared with perfusion blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other ASL acquisition times in recently published data, which ranged from 3 minutes, 26 seconds, to 5 minutes, 52 seconds, this results in an acceleration factor of approximately 3.5. 13,18 This acceleration was achieved as the result of the reduction of measurement repetitions to 25 rather than the formerly suggested 50 repetitions. 11,12 This was accomplished by the signal intensification of intravascular blood flow compared with perfusion blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…ASL perfusion measurements have been shown to have a high test-retest reliability. 9 In addition, ASL data were characterized as a reliable alternative to invasive measurement techniques, such as dynamic susceptibility MR imaging perfusion [10][11][12][13][14] and positronemission tomography. 15 There are also some weaknesses of this perfusion technique.…”
mentioning
confidence: 99%
“…In the past, there have been several brain tumor studies that compared ASL CBF with DSC rCBF (11,21,22) or with both DSC rCBF and rCBV parameters (12,13,23,24). The present study included comparisons of ASL CBF with additional DSC MRI parameters, including Tmax and MTT.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of perfusion MR imaging with arterial spin-labeling (ASL) for assessing brain tumor angiogenesis and grading gliomas has been evaluated. [2][3][4][5][6][7] DTI provides information on anisotropy, including fractional anisotropy (FA), and ADC. A recent study investigating DTI of gliomas showed that the FA and ADC tumor/normal tissue ratios are possible indicators of glioma proliferation and/or grading.…”
mentioning
confidence: 99%